RISK ASSESSMENT OF INVASIVE ALIEN PLANT SPECIES IN PANGANDARAN NATURE RESERVE, WEST JAVA - Mukhtar Hasbi, Arif
As a member of Convention on Biological Diversity (CBD), Indonesia has confirmed to prevent, control and eradicate Invasive Alien Species (IAS) in order to maintain biodiversity. Pangandaran Nature Reserve (PNR) is one of conservation areas that have been invaded by IAS plants. However, ineffective control methods of invasive plant species lead to the persistence of these species in this area. Therefore, this study is conducted to identify and assess risk status of invasive plant species, and propose recommendation strategy to manage them. 60 plots of 10m x10 m, 5m x5 m, and 1m x1m were established in six areas (Pasir putih, Cikamal, Cirengganis, Badeto, Nanggorak, and Batu meja) to clarify species composition. Then, IAS plants are grouped based on invasive species databases (CABI, GISD, PIER, and KMTB BIOTROP). Risk and feasibility indices were calculated based on risk assessment protocol to determine recommendation strategy to control IAS plants. Cikamal has the highest number of IAS plants (9 out of 11 species from total IAS plants in PNR) i.e. Tectona grandis, Chromolaena odorata, Cynodon dactylon, Melastoma.malabathricum, Chrysopogon aciculatus, Fimbristylis monostachya, Cyperus sp., Elephantopus scaber, and Axonopus compressus. Six IAS plants with high important index were selected to be assessed. Risk and feasibility indices and recommendation strategy to manage IAS plants are respectively T. grandis (169.2; 192; manage species), C. odorata (149.46; 105.6; manage species), C. dactylon (100.8; 120.45; manage location), M. malabathricum (76.8; 47.52; manage location), C. aciculatus (42.88; 49.89; manage location), F. monostachya (15.04; 20.19; monitoring). T. grandis has the highest risk of invasiveness, but it has low feasibility to be controlled. Thus, T. grandis and C. odorata will be priority IAS plants to be managed in PNR, especially Cikamal grassland.